Do Antiplatelet and Anticoagulation Agents Matter after Repair of Traumatic Arterial Injuries?. Issue 10 (October 2016) - Wang, Eugene; Inaba, Kenji; Cho, Jayun; Byerly, Saskya; Rowe, Vincent; Benjamin, Elizabeth; Lam, Lydia; Demetriades, Demetrios
Thrombosis is a devastating complication after repair of traumatic vascular injury. Although thrombosis rates have been described, the value of anticoagulation in preventing postrepair thrombosis is unknown. We hypothesize that postoperative anticoagulation reduces thrombosis rates. A total of 1524 consecutive patients with traumatic arterial injuries from January 2005 to June 2015 were identified, and 381 patients underwent the following repair types: direct suture of vessel wall, primary anastomosis, extra-anatomic reconstruction, tissue and synthetic interposition reconstruction. Twenty six patients received postoperative heparin at therapeutic levels, and 29 patients received postoperative aspirin for five consecutive days. The heparin and aspirin groups were matched with patients without postoperative anticoagulation by the following variables: anatomic arterial injury, type of vascular repair, and age. These groups were then compared using the following outcome measures: mortality, thrombosis of repaired vessel, amputation, hemorrhage, cerebral vascular accident, and extremity compartment syndrome. The demographics between the heparin, aspirin, and respectively matched groups were not statistically different. There was no statistically significant difference in the rate of thrombosis, bleeding, compartment syndrome, cerebral vascular accident, limb amputation, or mortality. Although there was no increase in bleeding complications with the use of heparin or aspirin, there was also no impact on the rate of thrombosis.